Maternal food consumption during pregnancy and asthma, respiratory and atopic symptoms in 5‐year‐old children - Willers, S M (BMJ Group, 2007)
BACKGROUND: Associations between maternal vitamin E, vitamin D and zinc intakes during pregnancy and asthma, wheeze and eczema in 5‐year‐old children have previously been reported. A study was undertaken to investigate whether maternal intake of specific foods during pregnancy is associated with asthma and allergic outcomes in the same children. METHODS: A longitudinal birth cohort study was conducted in 1924 children born to women recruited during pregnancy. Maternal diet during pregnancy was assessed by food frequency questionnaire (FFQ). Cohort children were followed up at 5 years by symptom questionnaire and FFQ. Food groups of interest were fruit, vegetables, fruit juice, whole grain products, fish, dairy products and fat spreads. Trends across outcome groups defined by level of food intake are presented. RESULTS: 1253 children participated at 5 years and maternal FFQ data were available for 1212. No consistent associations were found between childhood outcomes and maternal intake of the analysed foods except for apples and fish. Maternal apple intake was beneficially associated with ever wheeze (OR highest vs lowest tertile 0.63, 95% CI 0.42 to 0.95), ever asthma (OR 0.54, 95% CI 0.32 to 0.92) and doctor‐confirmed asthma (OR 0.47, 95% CI 0.27 to 0.82) in the children. Maternal fish consumption was beneficially associated with doctor‐confirmed eczema (OR ⩾1/week vs never 0.57, 95% CI 0.35 to 0.92). CONCLUSION: There was no evidence for associations between maternal intake of most foods during pregnancy and asthma, respiratory and allergic outcomes in 5‐year‐old children, except for apples and fish. Consumption of apples and fish during pregnancy may have a protective effect against the development of childhood asthma and allergic disease.